Bacterial metabolites of diet-derived lignans and isoflavones inversely associate with asthma and wheezing - Cardet, Juan-Carlos; Johns, Christina B.; Savage, Jessica H. (Journal of allergy and clinical immunology, 2015)
A total of 9633 subjects aged 6 to 85 years had complete data for the primary analyses of the association between urinary levels of lignan and isoflavone metabolites (eg, enterolactone, equol, and O-DMA) and physician-diagnosed current asthma and self-reported nonasthmatic wheeze, adjusting for age, sex, race/ethnicity, log-transformed urinary creatinine level, poverty index ratio (PIR), and body mass index (BMI). Several epidemiologic and laboratory-based studies have demonstrated associations between bacterial flora and lower respiratory tract disease.6 The presence of specific organisms and the diversity of microflora are thought to be relevant in this relationship.\n001 >=25-30 28 28 Â >30 29 26 Â PIR Â Â Â >=1 84 83 .07 Current asthma Â Â Â Yes 8 8 .27 Nonasthmatic wheeze Â Â Â Yes 9 9 .58 Sensitization to environmental aeroallergens Â Â Â Yes[low *] 43 44 .44 Table E9 Demographic characteristics and outcomes in subsample with data available for urinary lignans and isoflavones and subsample with data not available for urinary lignans and isoflavones Metabolite Tertile Current asthma Nonasthmatic wheeze Adjusted OR[low *] Adjusted OR[low *] Enterolactone 1 1 1 Â 2 0.58 (0.45-0.75) 0.69 (0.51-0.94) Â 3 0.64 (0.62-0.79) 0.56 (0.43-0.72) O-DMA 1 1 1 Â 2 1.14 (0.94-1.40) 0.88 (0.69-1.11) Â 3 0.10 (0.88-1.39) 0.75 (0.59-0.95) Equol 1 1 1 Â 2 1.05 (0.85-1.31) 1.22 (0.98-1.52) Â 3 1.25 (1.00-1.57) 1.13 (0.90-1.45) Table E10 ORs (and 95% CI) for asthma and wheeze by level of urinary metabolites of lignans and isoflavones, adjusting for all metabolites Values in boldface are statistically significant (P < .05).